Minimum Legal Age of Nonmedical Cannabis Purchase Laws and Cannabis-Related Hospitalizations in Canada, 2015 to 2022. - Myran, Daniel T.; Talarico, Robert; Pacula, Rosalie Liccardo; Xiao, Jennifer; Manuel, Doug; Hobin, Erin; Konikoff, Lauren; Tanuseputro, Peter; Taljaard, Monica (American Journal of Public Health, 2025)
Objectives. To determine whether the minimum legal age (MLA) for cannabis purchases is associated with reductions in cannabis-related hospitalizations in youths. Methods. We performed a population-based study examining all hospitalizations for cannabis use in Canada for individuals aged 15 to 44 years (n = 14.6 million in 2018) between January 1, 2015, and March 31, 2022. MLAs varied across Canada. We used a controlled interrupted time series design to compare changes in cannabis-related hospitalizations between individuals above and below the MLA. Results. There were 137 901 cannabis-related hospitalizations during the study. Prelegalization rates of hospitalizations were increasing by 2% per quarter for individuals above and below the MLA. After legalization, hospitalizations began declining by 2% per quarter in individuals below the MLA (rate ratio [RR] quarterly slope change = 0.96; 95% confidence interval [CI] = 0.95, 0.98) with no slope change for individuals above the MLA. The total effect, 3.5 years after legalization, was a 34% reduction (relative difference = 0.66; 95% CI = 0.49, 0.91; P =.011) in hospitalizations for those below relative to those above the MLA. Conclusions. Nonmedical cannabis legalization in Canada was associated with reductions in cannabis-related hospitalizations for youths below the MLA and with ongoing increases for individuals above the MLA. Public Health Implications. The results suggest that cannabis legalization may increase cannabis-related hospitalizations in adults but that MLAs may prevent such increases for at-risk young people in regions pursuing cannabis legalization.